Transforming waste to strength: Experimental study and performance evaluation of tire-derived aggregate concrete for sustainable building solutions - Oscar O. Rodezno; Johan Rodriguez; Maryam Nazari (Case Studies in Construction Materials)
Concrete contributes approximately 8 % of global CO₂ emissions annually, prompting the search for sustainable alternatives. Tire-derived aggregate concrete (TDAC), a material that incorporates recycled tire waste, offers benefits such as enhanced energy absorption and reduced weight. However, its mechanical strength is limited by weak bonding between rubber particles and cement paste. This study, conducted in two phases, aims to optimize TDAC’s material properties for structural applications. In Phase I, fine (FTDA), coarse (CTDA), and well-graded (WTDA) tire-derived aggregates were used to partially replace sand and gravel at ratios of 15 %, 30 %, 60 %, and 80 %. WTDA at a 30 % replacement ratio exhibited the highest Performance Index (PI), achieving a target slump of 76.2 mm with minimal compressive strength reduction compared to traditional concrete. Flexural tests showed that CTDA at a 60 % replacement ratio had the highest toughness, with a 12.34 % improvement over the baseline mix. Phase II focused on enhancing TDAC through pre-treatments, supplementary cementitious materials (SCMs), fiber reinforcements, and adjusted water-cement ratios with plasticizers, using the Phase I TDAC mix at 60 % replacement ratio as the baseline. Results indicated that NaOH pre-treatment of TDA increased compressive strength by 26.15 %. A mix with a 0.45 water-cement ratio and 0.4 % superplasticizer improved compressive strength by 75.4 % while maintaining workability. Among SCMs, slag increased compressive strength by 28.61 % and slump by 44.1 %. Fiber reinforcements increased toughness, with steel fibers enhancing it by 465.6 % and synthetic fibers by 71.1 %. The final optimized TDAC mix demonstrates balanced strength, workability, and toughness, showing potential for seismic applications.